Data Visualization for Students’ Perception Toward Online and Offline Learning in Information Technology Education Program - Sulidar Fitri; Toafik Muhammad; Cecep Riki; Sivaperumal Sampath (International Journal of Quantitative Research and Modeling, 2023)
The comments from student about online and offline learning can be analyzed to evaluate the learning process learning quality. This study focused on visualizing the data from students' perception comments especially one class in Information Technology Education Program between face-to-face learning and online learning. The learning process is observed in order to gain some insight about the difference number of words appearance in the word cloud. The comparative results of this research will be described through data visualization in word cloud using orange software. The results of this study indicate that the words appear in the comments of students who fill out the survey form display more words refer to their choices to take offline learning compared to online learning.